2022
DOI: 10.1002/pros.24292
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐repair status should be assessed in treatment‐emergent neuroendocrine prostate cancer before platinum‐based therapy

Abstract: Objectives This study sought to provide contemporary data from a multi‐institution with respect to DNA‐repair genes (DRGs) status and its impact on effects of platinum‐based chemotherapy in treatment‐emergent neuroendocrine prostate cancer (t‐NEPC), for which little data exist. Patients and Methods All patients were retrospectively collected with eligible biopsied tissues for targeted next generation sequencing (NGS). The main outcomes were radiologic progression‐free survival and overall survival according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The main characteristics of the eligible studies are shown in Table 1. Overall, 14 studies with 449 patients were included in the meta‐analysis 3,8–10,16–25 . The median number of patients enrolled in each study was 17 (range: 5–218), and the median age ranged from 65 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The main characteristics of the eligible studies are shown in Table 1. Overall, 14 studies with 449 patients were included in the meta‐analysis 3,8–10,16–25 . The median number of patients enrolled in each study was 17 (range: 5–218), and the median age ranged from 65 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 14 studies with 449 patients were included in the meta‐analysis. 3 , 8 , 9 , 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The median number of patients enrolled in each study was 17 (range: 5–218), and the median age ranged from 65 to 77 years. Eleven studies performed gene sequencing on tumour tissues, two studies conducted liquid biopsies (circulating tumour cells and cell‐free DNA), and one study did not report the source of tumour DNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations